Atomic Layers: Tellurium‐Assisted Epitaxial Growth of Large‐Area, Highly Crystalline ReS2 Atomic Layers on Mica Substrate (Adv. Mater. 25/2016). Issue 25 (3rd July 2016) - Cui, Fangfang; Wang, Cong; Li, Xiaobo; Wang, Gang; Liu, Kaiqiang; Yang, Zhou; Feng, Qingliang; Liang, Xing; Zhang, Zhongyue; Liu, Shengzhong; Lei, Zhibin; Liu, Zonghuai; et al.
Abstract : H. Xu, J. Zhang, and co‐workers synthesize anisotropic 2D‐layered rhenium disulfide with high crystal quality and uniform monolayer thickness. As described on page 5019, tellurium‐assisted epitaxial growth on a mica substrate is chosen to generate such structures.